2018
DOI: 10.1002/mar.21133
|View full text |Cite
|
Sign up to set email alerts
|

How well will this brand work? The ironic impact of advertising disclosure of body‐image retouching on brand attitudes

Abstract: Prior research has demonstrated various effects of exposure to thin-idealized models in advertisements on consumers' product evaluations. Although this past research provides important insights, it does not take into account that many of these thin-idealized images have been digitally manipulated. The present work studies the consequences of disclosure of this digital manipulation and the process consumers engage in when evaluating the brands responsible for these advertisements. We demonstrate that retouched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 69 publications
(84 reference statements)
1
20
0
1
Order By: Relevance
“…Furthermore, with a few exceptions (DeCarlo, ; Isaac & Grayson, ; Rozendaal et al, ; Semaan et al, ; Wei, Fischer, & Main, ), past persuasion knowledge research has tended to hypothesize and demonstrate that, when the likelihood of accessing conceptual persuasion knowledge increases, consumers become more skeptical (i.e., more distrusting and disbelieving), which leads to more negative perceptions of the persuasion agent, the persuasive message, and/or the product or brand being advertised. For example, Boerman et al () found that disclosing a company's sponsorship of a television program increased the likelihood of conceptual persuasion knowledge access among participants, which led to beliefs that the product‐related content in the program was biased, dishonest, and not credible.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, with a few exceptions (DeCarlo, ; Isaac & Grayson, ; Rozendaal et al, ; Semaan et al, ; Wei, Fischer, & Main, ), past persuasion knowledge research has tended to hypothesize and demonstrate that, when the likelihood of accessing conceptual persuasion knowledge increases, consumers become more skeptical (i.e., more distrusting and disbelieving), which leads to more negative perceptions of the persuasion agent, the persuasive message, and/or the product or brand being advertised. For example, Boerman et al () found that disclosing a company's sponsorship of a television program increased the likelihood of conceptual persuasion knowledge access among participants, which led to beliefs that the product‐related content in the program was biased, dishonest, and not credible.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…However, frequent exposure to commercial persuasion can also lead to more adaptive outcomes, including greater knowledge and understanding about how marketing tactics work and thus a more sophisticated ability to cope with persuasion attempts (e.g., Boush, Friestad, & Rose, ). Researchers refer to this knowledge and understanding as “persuasion knowledge” (Friestad & Wright, , ) or “advertising literacy” (Rozendaal, Opree, & Buijzen, ; Young, ), and it has been the focus of considerable investigation over the past two decades (e.g., Campbell & Kirmani, ; Carlson, Bearden, & Hardesty, ; Hibbert, Smith, Davies, & Ireland, ; Kirmani & Zhu, ; Semaan, Kocher, & Gould, ; Wentzel, Tomczak, & Herrmann, ; Xie & Johnson, ). Because the terms “persuasion knowledge” and “advertising literacy” are often used synonymously (e.g., Tutaj & van Reijmersdal, ; Wright, Friestad, & Boush, ), we opt in this paper to use the former term exclusively to refer to knowledge structures related to persuasion episodes.…”
Section: Introductionmentioning
confidence: 99%
“…The anthropomorphic image with high congruence has a strong correlation with the product. Through the image display, the connotation and significance of the advertising image will be transferred to the product (Semaan et al, 2008). Consumers associate advertising image with products and expand the connotation of personification image.…”
Section: Schema Theory Association Network Model and Anthropomorphic Image Congruencementioning
confidence: 99%
“…La innovación del producto figura como una parte importante para comprender el comportamiento del consumidor y sus preferencias por el lugar de origen (Sahagun y Vasquez-Parraga, 2018; Fernández-Ferrín, Bande-Vilela, Klein y del Río-Araújo, 2015). Por otra parte, las estrategias de promoción pueden tener un impacto positivo o negativo según la táctica empleada (Gong y Tung, 2017;Semaan, Kocher y Gould, 2018). Por lo tanto, el grado de conocimiento que el consumidor tiene del producto y cómo percibe esta relación a través de la publicidad tendrá un impacto en su intención de compra.…”
Section: Factores Externos Al Valor Percibidounclassified